Analisis Sistem Penyaluran Bantuan Ke Desa Pada Lingkungan Kabupaten Di Propinsi Kalimantan Barat - Rayadi Rayadi (Jurnal Ekonomi Integra, 2016)
Management or utilization of aid efficiently and effectively will be able to change the state of underdevelopment and low into the progress and higher. Management of grants must be really focused for poor areas and poor people. Poverty reduction programs in Indonesia is necessary to find a method of evaluation and appropriate monitoring so that the quality of the implementation of poverty reduction programs become better future will come and actually can be used as the basis of government programs to the welfare of society.